Quo Vadis Hukum Keluarga Islam dalam KHI dan Upaya Desakralisasi untuk Relevansi Seiring Modernitas dan Keindonesiaan - Sadari Sadari (JURNAL INDO-ISLAMIKA, 2015)
This article reveals the fact that in Islamic Family Law, there are a number of anomalies and crisis, for instance, Islamic Law Compilation (KHI) on polygamy and mixed-religion marriage which contains discrimination and intolerance. This, however, is caused by its enforcement bound by civil law and merely to theMoslem communities. The article introduces the nationalization and internationalization of Islamic family law in the KHI, thus eliminating discrimination and intolerance. This will be sought by creating coherence between KHI and modernity issues such as: Human Rights, democracy, civil society, nation state and constitutionalism in the effort to desacralization. When added with the term desacralization, it will mean to liberate people from superstitious constraints (mythology) in some aspects, yet reserving the sacralization, not undermining or abandoning religious orientation in the norms and values of society, especially in the Islamic Family Law. Understanding this fundamental, desacralization of Islamic family law is, hence, Quo Vadis Islamic Family Law, that will eventually create progressive Islamic Family Law consistent with modernity and Indonesian ideology